EFFECT OF TEMPERATURE ON THE CONSUMPTION CAPACITY OF CHRYSOPERLA CARNEA (STEPHENS) (NEUROPTERA: CHRYSOPIDAE) REARED ON FOUR APHID SPECIES - RENU YADAV; P. H. PATHAK (The Bioscan, 2010)
Effects of prey kinds on consumption capacity was studied in the common lacewing, Chrysoperla carnea using four aphid species i.e. Aphis craccivora, Aphis gossypii, Myzus persicae and Lipaphis erysimi, as a prey, at five constant temperature regimes that is 10ºC, 15ºC, 20ºC, 25ºC and 30ºC under laboratory conditions. The failures of aphid’s chemical control compel us to switch over other methods of integrated pest management (IPM), particularly biological control programme through larvae of C. carnea, a predator of several arthropod pest. The data revealed that the consumption capacity of C. carnea differ significantly, when its larvae were reared separately on the four aphid species at different temperatures. Consumption was maximum (320.5±22.79 aphids) at 15ºC when A. craccivora was given as prey to the larvae of this predator and minimum (143.3±1.25 aphids) at 30ºC when reared on L. erysimi.